Comparable properties of native K channels in the atrium and ventricle of snails - Kodirov, Sodikdjon; Herbinger, Tobias; Rohwedder, Arndt (Comparative biochemistry and physiology. Part C, Toxicology & pharmacology, 2024)
Mollusks, including snails, possess two chambered hearts. The heart and cardiomyocytes of snails have many similarities with those of mammals. Also, the biophysics and pharmacology of Ca, K, and Na ion channels resemble. Similar to mammals, in mollusks, the ventricular cardiomyocytes and K channels are often studied, which are selectively sensitive to antagonists such as 4-AP, E-4031, and TEA. Since the physiological properties of the ventricular cardiac cells of snails are well characterized, the enzymatically dissociated atrial cardiomyocytes of Cornu aspersum (Müller, 1774) were studied using the whole-cell patch-clamp technique for detailed comparisons with mice, Mus musculus. The incubation of tissues in a solution simultaneously containing two enzymes, collagenase and papain, enabled the isolation of single cells. Recordings in the atrial cardiomyocytes of snails revealed outward K+ currents closely resembling those of the ventricle. The latter was consistent, whether the voltage ramp or steps and long or short pulses were used. Interestingly, under identical conditions, the current waveforms of atrial cardiomyocytes in snails were similar to those of mice left ventricles, albeit the kinetics and the absence of inward rectifier K channel (IK1) activation. Therefore, the heart of mollusks could be used as a simple and accessible experimental model, particularly for pharmacology and toxicology studies.
Online verfügbar: 8. Mai 2024, Artikelversion: 14. Mai 2024
Gesehen am 18.11.2024